2015
DOI: 10.1103/physrevb.91.085430
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal AlN: Dimensional-crossover-driven band-gap transition

Abstract: Motivated by a recent experiment that reported the successful synthesis of hexagonal (h) AlN [Tsipas et al., Appl. Phys. Lett. 103, 251605 (2013)], we investigate structural, electronic, and vibrational properties of bulk, bilayer, and monolayer structures of h-AlN by using first-principles calculations. We show that the hexagonal phase of the bulk h-AlN is a stable direct-band-gap semiconductor. The calculated phonon spectrum displays a rigid-layer shear mode at 274 cm −1 and an E g mode at 703 cm −1 , which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
126
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(147 citation statements)
references
References 62 publications
21
126
0
Order By: Relevance
“…As the applied strain increases, the energy difference between two valence band edges also increases. A similar shift in VBM of hexagonal aluminium nitride (h-AlN) was reported by Bacaksiz et al [30]. The VBM of GaS consists of p z orbitals of the Ga and S atoms.…”
Section: Structural and Electronic Propertiessupporting
confidence: 48%
“…As the applied strain increases, the energy difference between two valence band edges also increases. A similar shift in VBM of hexagonal aluminium nitride (h-AlN) was reported by Bacaksiz et al [30]. The VBM of GaS consists of p z orbitals of the Ga and S atoms.…”
Section: Structural and Electronic Propertiessupporting
confidence: 48%
“…Although bulk h-AlN is a direct gap insulator, it was recently shown that its layered structure reveals an indirect gap character up to ten layers [45]. The differences in the band splittings of bulk and layered h-AlN were stressed previously, which implies that diversity in the optical spectra should also be expected.…”
Section: B Layer-dependent Optical Properties Of H-alnmentioning
confidence: 98%
“…For h-AlN, the main absorption peak of the calculated spectrum is situated around 8.6 eV, where the absorption phenomenon occurs the most intensely. The onset of interband absorption resides near 4.4 eV, which appears slightly higher than the direct band gap of 3.4 eV [45], where the difference most probably results from further band-to-band transitions with higher energy values. Another feature is the shoulder structure around both 6.8 eV and 7.3 eV.…”
Section: A Optical Properties Of Bulk Aln Crystalmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction of free-standing SL GaN and AlN in planar honeycomb structure, i.e., h-AlN and h-GaN, have initiated several theoretical studies attempting to reveal their mechan-* seymur@unam.bilkent.edu.tr † ciraci@fen.bilkent.edu.tr ical, electronic, and optical properties [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. While 3D wurtzite GaN (wz-GaN) is a direct-band-gap semiconductor and corresponds to a global minimum, SL h-GaN has relatively larger indirect fundamental band gap [21].…”
Section: Introductionmentioning
confidence: 99%